Motivasi Kerja Mahasiswa Laki-laki Berjualan Online Produk Kecantikan - Nuri Lusiana; Sri Respati Andamari (UIN Sunan Kalijaga, 2016)
Online shop is a quiet promising bussiness to earn profit. There are 82 millions internet user in Indonesia, it’s about 30% from Indonesia’s population. Gender isn’t an issue to become cosmetic online shop vendor. This research is conducted to reveal the factors that affect male college students motivation to become cosmetic online shop vendor, this research uses qualitative method with parcitipative observation and semi-structured interview. Result shows that all subjects’ motivation in this research are almost related to perception, self-esteem, and achievement, expectation, needs, work satisfaction, work type and characteristic, workgroup, work environment,and profit. Work group was not affecting the motivation, therefore not related with motivation.